2021
DOI: 10.1186/s42834-021-00084-w
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of residual chlorine in a drinking water network in times of pandemic of the SARS-CoV-2 (COVID-19)

Abstract: Due to the outbreak of the novel coronavirus disease there is a need for public water supply of the highest quality. Adequate levels of chlorine allow immediate elimination of harmful bacteria and viruses and provide a protective residual throughout the drinking water distribution network (DWDN). Therefore, a residual chlorine decay model was developed to predict chlorine levels in a real drinking water distribution network. The model allowed determining human exposure to drinking water with a deficit of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
20
0
2
Order By: Relevance
“…Appropriate knowledge of the behaviour of FRC concentration as it travels through water distribution systems assists in meeting the minimum and maximum residual disinfectant levels allowed by regulations and also ensures the quality of the water reaching the population. According to the World Health Organization (WHO), water contamination can occur by viruses classified as moderately and highly harmful to health: Hepatitis A and E, rotavirus and more recently the coronavirus (García-Ávila et al, 2021). Thus, public water systems are required to monitor the behaviour and the disinfectant concentration to maintain acceptable levels in more distant areas and to meet the minimum residual chlorine concentration throughout the day, ranging from 0.10 mg L -1 to 0.20 mg L -1 (Ozdemir and Buyruk, 2018;Ababu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate knowledge of the behaviour of FRC concentration as it travels through water distribution systems assists in meeting the minimum and maximum residual disinfectant levels allowed by regulations and also ensures the quality of the water reaching the population. According to the World Health Organization (WHO), water contamination can occur by viruses classified as moderately and highly harmful to health: Hepatitis A and E, rotavirus and more recently the coronavirus (García-Ávila et al, 2021). Thus, public water systems are required to monitor the behaviour and the disinfectant concentration to maintain acceptable levels in more distant areas and to meet the minimum residual chlorine concentration throughout the day, ranging from 0.10 mg L -1 to 0.20 mg L -1 (Ozdemir and Buyruk, 2018;Ababu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rossman (2000), the water quality simulation model allows monitoring the growth or decay of a substance due to reactions as it moves along the water distribution network. Chlorine decay models are useful for managers of drinking water supply systems to predict the residual chlorine concentration across the network under various hydraulic conditions (García-Ávila et al, 2021). The degradation of the FRC can be modeled by some known computer software that simulates the hydraulic behavior and water quality in distribution networks.…”
Section: Introductionmentioning
confidence: 99%
“…This type of climate is highly conducive to the breeding and spreading of bioaerosols (Tsai and Liu 2009). Moreover, recent spread of COVID-19 worldwide shows that drinking water disinfection (Garcia-Avila et al 2021) and indoor air purification are extremely important and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…WHO recommended that the residual concentration of free chlorine should be !0.5 mg/l after at least 30 min of contact time at pH , 8.0 for effective centralized disinfection. García-Ávila et al (2021) developed a drinking water distribution network model for a part of Azogues City, Ecuador, using EPANET software (Rossman 2000) and found that about 45% of the model nodes did not comply with the WHO recommendation. Thus, it is important to assess and optimize the quantity of chlorine in water distribution networks, e.g., Javadinejad et al (2019), Lipiwattanakarn et al (2021).…”
Section: Introductionmentioning
confidence: 99%